2012
DOI: 10.1088/0957-4484/23/15/155302
|View full text |Cite
|
Sign up to set email alerts
|

Angle dependent optical properties of polymer films with a biomimetic anti-reflecting surface replicated from cylindrical and tapered nanoporous alumina

Abstract: Anodic porous alumina nanostructures have been fabricated with tapered and cylindrical pores with a spacing of 100 and 200 nm and depth of 180-500 nm. The porous nanostructures were replicated into polymer films to create a moth-eye anti-reflecting surface by a roll-to-roll UV replication process. The angle dependent optical transmission of the resulting polymer films exhibited up to a 2% increase in transmission at a normal angle and up to a 5% increase in transmission at a 70° angle of incidence to an equiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The same structures were further optimized by a parametric variation of the angle of the p-AAO tapered pores, with the conclusion that the AR structures with a gradually changing slope exhibited the lowest reflectance [137]. A more elaborated evolution of this idea, with a view to industrial up-scaling is found in [138], in which p-AAO nanostructures with tapered and cylindrical pores are fabricated with spacing of 100 and 200 nm and depth of 180-500 nm, and then replicated into polymer films by a roll-to-roll process. By means of angle-dependent optical transmission measurements, they concluded that the structures provide up to a 2 % increase in transmission at normal incidence and up to a 5 % increase at 70º incidence, with respect to an equivalent flat surface.…”
Section: Porous Anodic Aluminum Oxide In Photon-energy Conversionmentioning
confidence: 99%
“…The same structures were further optimized by a parametric variation of the angle of the p-AAO tapered pores, with the conclusion that the AR structures with a gradually changing slope exhibited the lowest reflectance [137]. A more elaborated evolution of this idea, with a view to industrial up-scaling is found in [138], in which p-AAO nanostructures with tapered and cylindrical pores are fabricated with spacing of 100 and 200 nm and depth of 180-500 nm, and then replicated into polymer films by a roll-to-roll process. By means of angle-dependent optical transmission measurements, they concluded that the structures provide up to a 2 % increase in transmission at normal incidence and up to a 5 % increase at 70º incidence, with respect to an equivalent flat surface.…”
Section: Porous Anodic Aluminum Oxide In Photon-energy Conversionmentioning
confidence: 99%
“…The surface free energy of TPU-AGF-Green1 was calculated using the reported surface free energy components of water, n-hexadecane, and diiodomethane, together with the experimental contact angles of water, n-hexadecane, and diiodomethane on TPU-AGF-Green1 layer in Owens who extended the Fowkes concept. [16][17][18] The surface free energy of TPU-AGF-Green1 was 43 mJ∕m 2 . The structure of sugarrelated organic compounds derived from biomass contributes to lowering the viscosity, while the photocurable acryloyl groups in TPU-AGF-Green1 provide an acceptable surface free energy in the fundamental evaluation of eco-friendly antiglare film with liquid glucose and trehalose derivatives.…”
Section: Preparation Of Sugar-related Organic Compoundsmentioning
confidence: 99%
“…1 Anodic porous alumina nanostructures have been fabricated with tapered and cylindrical pores for a biomimetic antireflecting surface. 2 3-(Trimethoxysilyl) propyl methacrylate and fluoroalkylsilane modified silica particles were developed for antiglare film. 3 The effects of the solvents in coatings and process temperature on the haze of antiglare films were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, AAOs with tapered pores and pitch size in the range of 100-490 nm were fabricated [21][22][23][24][25][26][27]. The tapered-pore AAO is very attractive porous material because it can act as a layer for the gradually changing refractive index.…”
mentioning
confidence: 99%